A Review on Fog Computing Systems - Farhoud Hosseinpour; Yan Meng; Tomi Westerlund; Juha Plosila; Ran Liu; Hannu Tenhunen (Advanced Institute of Convergence Information Technoogy, 2022)
The current decade has witnessed a wide deployment of Internet of Things (IoT) technology in various application domains, and its pervasive role will continue to strengthen in the future. For dealing with a vast number of connected devices and the big data generated by them, an efficient computing platform is required. Fog computing has been proposed as a solution. It is a paradigm extending cloud computing and services to the edge of the network, thus reducing the latency of dynamic decision making and improving real-time performance in general. This paper provides a view on the current state-of-the-art research in the area of fog computing and internet of things (IoT) technology.